The farming costs (including insurance) of the agricultural holdings in the European Union - Arych, Mykhailo; Kuievda, Yulia; Dvořák, Marek; Hinke, Jana (My University, 2023)
The paper is devoted to exploring the farming costs (including insurance) indicators of the agricultural enterprises in the European Union. The analysis employs the box plot methodology that provides a five-number summary for a set of data. In this paper, we analyse the evidence of interconnection between the indicators of efficiency and competitiveness and insurance costs regarding food market security. This research discusses the dynamic changes of the absolute value of farming costs (including insurance) indicators and different relative indicators derived from the original one for the agricultural enterprise holdings in the European Union for the period of 2004-2019. The results show that farming costs (including insurance) indicators of the agricultural holdings should be considered as an instrument for providing food market security. Based on these research results, we are going to further explore the impact of insurance on the food market security. In addition, these research results could help to clarify the difference between EU countries and dynamic changes in farming costs (including insurance) indicators of agricultural holdings. У статті досліджено показники витрат на ведення сільського господарства (включаючи страхування) сільськогосподарських підприємств у Європейському Союзі. Під час аналізу використовується методологія прямокутної діаграми, яка надає зведення з п’яти чисел для набору даних. У цій статті ми аналізуємо докази взаємозв’язку між показниками ефективності і конкурентоспроможності та витратами на страхування. У статті обговорюються динамічні зміни абсолютного значення показників витрат на ведення сільського господарства (включаючи страхування) та різних відносних показників, отриманих сільськогосподарських підприємств у Європейському Союзі за період 2004-2019 рр. Результати показують, що показники витрат на ведення сільського господарства (включаючи страхування) агрохолдингів слід розглядати як інструмент забезпечення безпеки продовольчого ринку. На основі цих результатів дослідження ми збираємося продовжити дослідження впливу страхування на безпеку продовольчого ринку. Крім того, ці результати дослідження можуть допомогти з’ясувати різницю між країнами ЄС та динамічними змінами показників витрат на ведення сільського господарства (включаючи страхування) сільськогосподарських угідь.
Keywords: кафедра маркетингу; кафедра електропостачання і енергоменеджменту; аграрні підприємства; витрати; страхування; конкурентоспроможність; agricultural holdings; farming costs; insurance; competitiveness